Comparison of the Effectiveness of 10% Sulfur Soap and 2-4 Ointment as Single Treatment - Alief Ilman Zaelany; Ida Srisurani Wiji Astuti; Ika Rahmawati Sutejo (Journal of Agromedicine and Medical Sciences, 2017)
Scabies disease caused by Sarcoptes scabiei var. hominis mites has become a problem in a whole world especially in developing countries like Indonesia. Scabies has a very contagious nature especially in places with dense population levels like Islamic boarding school. Permethrin which is a drug of choice for scabies has a fairly expensive price so it is less effective when used in mass treatment. In Indonesia, sulfur preparations, especially 10% sulfur soap and 2-4 ointment are easy to obtain because the price is affordable and available at the community health clinic. The purpose of this study is to know the difference in effectiveness of 10% sulfur soap and 2-4 ointment as a single treatment and combination on scabies disease. In this clinical trial study, treatment was performed on 3 groups, 10% sulfur soap group (n=36), 2-4 ointment group (n=36) and combination group (n=36). The examination was done on days 8, 15 and 22. Data analysis using SPSS version 23 with chi-square test. The results showed that the highest recovery rate was in combination group (week-1 (22,22%), week-2 (63,89%) and week-3 (94,44%)) followed by 2-4 ointment group (week-1 (11,11%), week-2 (72,22%) and week-3 (88,89%)) and 10% sulfur soap group (week-1 (2,78%), week-2 (52,78%) and week-3 (75,0%). The results of the analysis comparing the 10% sulfur soap group with the combination group showed p value on all consecutive examinations p=0,013, p=0,339 and p=0,022. In the comparison 2-4 ointment group to the combination group obtained p value on all examinations respectively p=0,206, p=0,448 and p=0,394. The conclusion is combination therapy had the highest cure rate and statistically significant (p=<0,05) was obtained in comparison of 10% sulfur soap to combination at week-1 and week-3 examination. Keywords: scabies, comparison of the effectiveness, 10% sulfur soap, 2-4 ointment, combination, Islamic boarding school